Evaluation of clinical outcomes of patients with post-stroke wrist and finger spasticity after ultrasonography-guided BTX-A injection and rehabilitation training - Jiang, Li; Dou, Zu-Lin; Wang, Qing; Wang, Qiao-Yuan; Dai, Meng; Wang, Zhen; Wei, Xiao-Mei; Chen, Ying-Bei (Frontiers in Human Neuroscience, 2015)
Objective: Using ultrasonography (US) to guide botulinum toxin type A (BTX-A) injection in patients with post-stroke wrist and finger flexor muscle spasticity and assessing clinical outcomes after the injection and rehabilitation intervention. Methods: Twenty-three patients with wrist and finger spasticity after stroke were recruited in this study from May 2012 to May 2013. Under US guidance, the proper dose (250U) of BTX-A was injected into each spastic muscle at two injection sites. Then, conventional rehabilitation training started next day after BTX-A injection. The degree of spasticity was assessed by modified Ashworth scale (MAS) and wrist and finger motor function by active rang of movement (AROM), and Fugl-Meyer assessment (FMA) at the baseline, 1, 2, 4 and 12 weeks after BTX-A injection. Results: Significant decreases (p < 0.02) in the MAS scores of both the finger flexor muscle tone and wrist flexor muscle tone measured at 1, 2, 4, and 12 weeks after the BTX-A injection were found in comparison with the baseline scores. Compared with the baseline, the AROM values of the wrist and finger extensions and the FMA scores of the wrist and hand significantly increased (p < 0.02) at 2, 4 and 12 weeks after the BTX-A injection. Conclusions: US-guided BTX-A injection combined with rehabilitation exercise decrease spasticity of the wrist and finger flexor muscles and improve their motor function in stroke patients up to 12 weeks following BTX-A injection.